2021
DOI: 10.1093/hmg/ddab094
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibitors reduce enteropathy, intestinal bleeding and colectomy rate in patients with juvenile polyposis of infancy with PTEN-BMPR1A deletion

Abstract: Background Ultrarare genetic disorders can provide proof of concept for efficacy of targeted therapeutics and reveal pathogenic mechanisms relevant to more common conditions. Juvenile polyposis of infancy (JPI) is caused by microdeletions in chromosome 10 that result in haploinsufficiency of two tumor suppressor genes: phosphatase and tensin homolog deleted on chromosome 10 (PTEN) and bone morphogenetic protein receptor, type IA (BMPR1A). Loss of PTEN and BMPR1A results in a much more severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
(42 reference statements)
2
9
0
Order By: Relevance
“…This allowed for reduction in GI blood and protein loss, optimization of weight gain with successful weaning off PN while avoiding bowel resection. This is consistent with recently published data on patients with infantile JPS [ 5 ]. Even still, until this point, a full narrative account of a patient with infantile JPS, treated with sirolimus without need for bowel resection, had not been published.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This allowed for reduction in GI blood and protein loss, optimization of weight gain with successful weaning off PN while avoiding bowel resection. This is consistent with recently published data on patients with infantile JPS [ 5 ]. Even still, until this point, a full narrative account of a patient with infantile JPS, treated with sirolimus without need for bowel resection, had not been published.…”
Section: Discussionsupporting
confidence: 94%
“…Compared to its less severe counterpart of JPS, infantile JPS occurs much earlier in life with more severe disease manifestations. A study of 25 JPS patients noted that those presenting in infancy had higher polyp burden, greater risk of PLE and higher need for colectomy compared to those presenting after 1 year of age (relative risk (RR) for colectomy = 2.16, 95% confidence interval (CI) = 1.02 - 5.34, P = 0.03) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Regarding the efficacy of sirolimus on GIS findings in patients, successful results in decreasing the number and size of polyps have been demonstrated not only for PTEN point mutations but also for intragenic PTEN deletions and larger deletions encompassing both PTEN and BMRP1A. 26,[34][35][36][37] In another recent interventional study by Komiya et al 11 , a 56-day course of sirolimus treatment was well tolerated in patients with PHTS and was associated with some evidence of improvement in symptoms, skin and GI lesions, cerebellar function, and decreased mTOR signaling. Thus, mTOR inhibitor treatment was initiated in the present study, as a role of sirolimus was shown in several studies in patients with PHTS.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic variants in PTEN cause constitutive activation of AKT and subsequent upregulation of mTOR signaling, explaining the overgrowth and cancer predisposition associated with PHTS. For patients with JPI, mTOR inhibitors can reduce enteropathy, intestinal bleeding, and colectomy rate [57 ▪ ]. A pilot study showed that sirolimus in patients with Cowden syndrome improved symptoms, skin and gastrointestinal lesions, cerebellar function, and decreased mTOR signaling [58].…”
Section: Methodsmentioning
confidence: 99%